(untitled) (Geospatial Health, 2014)
The aim of the present study was to determine the role of specific environmental and climatic factors affecting the distribution and density of Phlebotomus ariasi and P. perniciosus, the proven vectors for Leishmania infantum in Spain. An entomological study was carried out in July 2006 in the province of Lleida with sticky traps set in their diurnal resting places at altitudes ranging from 86 to 1,755 m above the mean sea level (339 sites were sampled). Bivariate analysis revealed that factors such as altitude, bioclimatic zone, temperature, precipitation, sampling site (site relative to settlement, site situation, site category), wall vegetation, particular environment (in this case a natural park), general environment, adjacent natural vegetation and land cover were significantly associated with sand fly densities. The multivariate model for P. perniciosus revealed that its density was affected by site and land cover. Specifically, paved driveways correlated negatively with vector density (Incidence Risk Ratio (IRR): 0.41) and arable land cover correlated positively (IRR: 4.59). In the case of P. ariasi, a significant correlation was observed with the altitude and bioclimatic zone, with density increasing at >800 m above the mean sea level (IRR: 3.40) and decreasing in the meso-Mediterranean bioclimatic zone (IRR: 0.08). Both species were mostly found in agricultural and forest areas far from domestic environments. However, the two species correlated differently with altitude, bio-climate, vegetation, temperature and precipitation, which emphasises the importance of their individual analysis in studies regarding risk of leishmaniasis transmission.